Purification and properties of nitroalkane oxidase from Fusarium oxysporum. - Kido, T (1978)
A nitroalkane-oxidizing enzyme, which was inducibly formed by addition of nitroethane to the medium was purified to homogeneity from an extract of Fusarium oxysporum (IFO 5942) with an overall yield of about 20%. The enzyme catalyzed the oxidative denitrification of 1-nitropropane as follows: CH2(NO2)CH2CH3 + O2 + H2O leads to OHCCH2CH3 + HNO2 + H2O2. In addition to 1-nitropropane, 3-nitro-2-pentanol, 2-nitropropane, and nitrocyclohexane are good substrates; the enzyme is designated "nitroalkane oxidase" (EC class 1.7.3). The enzyme has a molecular weight of approximately 185,000 and consists of four subunits identical in molecular weight (47,000). Flavin adenine dinucleotide was required for the enzyme activity and could be replaced in part by riboflavin 5'-phosphate. The maximum reactivity was found at about pH 8.0. The enzyme was inhibited significantly by HgCl2, KCN, p-chloromercuribenzoate, and N-ethylmaleimide. The Michaelis constants are as follows: 1-nitropropane, 1.54 mM; 2-nitropropane, 7.40 mM; nitroethane, 1.00 mM; 3-nitro-2-pentanol, 3.08 mM; nitrocyclohexane, 0.90 mM; and flavin adenine dinucleotide, 1.33 micrometer.